Silicon in wheat crop under water limitation and seed tolerance to water stress during germination - Fontes Valory Gama, Guilherme; Bitencourt Teixeira Lima Brum, Laryssa; Silva Martins, Maycon; da Silva, Laércio Junio; Cunha Fernandes dos Santos Dias, Denise (Revista Ceres, 2025)
Water stress during wheat seed germination and seedling establishment for affect the percentage and speed of germination. Silicon (Si) is related to plant tolerance to different types of stress, then the application of this nutrient in the mother plant during seed production could contribute to the improvement of the seed quality and, consequently, its tolerance to stress. The aim was to evaluate the effect of foliar application of silicon on the tolerance of wheat seeds, produced under different irrigation levels, to water stress during germination and initial seedling growth. Wheat seeds were produced under three irrigation depths (0, 50 and 100% of the total required irrigation) applied after the anthesis. The silicon was supplied in two doses by foliar application (0 and 5 mM of Si). The germination and seedling growth were performed under water stress induced by PEG 6000 at the -0.2; -0.4; -0.6 MPa osmotic potentials. In addition, in the control only distilled water was used. The reduction of the osmotic potential reduced seed germination, germination speed and seedling growth. Irrigation depths, as well as foliar application of Si, during seed production did not influence the physiological quality and tolerance of seeds to water stress during germination.